Characteristics of drug-resistant staphylococci isolated from milk of lambed ewes during the perinatal period - Hahaj-Siembida Agata; Nowakiewicz Aneta; Greguła-Kania Monika; Bochniarz Mariola; Trościańczyk Aleksandra; Osińska Marcelina (Journal of Veterinary Research)
Staphylococci are still a challenge in veterinary medicine, as they are one of the aetiological factors causing clinical and subclinical mastitis in small ruminants. The aim of the study was to analyse the occurrence of staphylococci in milk obtained from Świniarka (SW) and Uhruska (UHR) sheep and to characterise their drug resistance and virulence.